The emergent transition to remote learning online: A study of the experience of students’ doing postgraduation in education - Navani, Manasi Thapliyal; Nag, Shivani (Voices of Teachers and Teacher Educators, 2021)
This paper attempts to examine and situate the experience of students enrolled in two postgraduate programmes in the discipline of education during the pandemic. The lockdown introduced in response to COVID-19 pandemic entailed a sudden and abrupt shift to the online mode of teaching. In order to understand the efficacy of the online classroom space for students preparing or studying to be teachers and teacher educators, it is important to reflect on the nature of the discipline of education and the current context in which the transition to online learning happened. This transition was not an outcome of a systematically planned academic experiment or endeavour. This paper builds upon narratives emerging from the responses of students pursuing postgraduate degrees in education, and early childhood care and education. The responses to an open-ended questionnaire, semester-end student feedback forms on courses taught in an online mode, periodic informal interactive sessions with students over a period of seven months, and participant observations conducted by the authors in a School of Education Studies in a university in New Delhi were gathered. The informal interactions and group discussions with students were facilitated by the authors’ location as faculty in the same department. The intersubjective space thus created between the participants and the researchers, allowed a closer engagement with everyday challenges and students’ reflections and experiences. The paper draws from the interpretive paradigm and attempts to examine how students experienced the digital pedagogic space and this transition to online learning.